Recent progress on anti-cancer activity of thiadiazoles: A review - C.R. Santhosh; Sampath Chinnam; Nagaraju Kottam; S Amreen; Guddekoppa S. Ananthnag; G.M. Madhu; Samata Gadde; Viola Tressa Fernandes; Haritha Arnipalli (Results in Chemistry)
Cancer, a life-threatening condition which has become one of the deadliest disease impacting human health. Conventional drugs have significant side effects and are prone to drug resistance, whereas innovative therapies are costly and place a large load on patients. Despite the fact that several decades of medication research and discovery have produced a number of helpful chemotherapeutic drugs, the hunt for novel chemical entities with enhanced efficacy and safety is still ongoing. Thiadiazoles acts as inhibitors against several specific enzymes or signaling pathways. These compounds are frequently utilized when combined with other anti-cancer drugs to improve their efficacy. Thiadiazoles exhibit beneficial synergistic effects when used with other anticancer treatments like chemotherapy or targeted therapy. They have shown considerable anti-cancer action against various cancer cell lines. The review covers recent anti-cancer research findings from 2021 to 2024. This review aimed to give an overall description of thiadiazoles and analogs which demonstrated potential anti-cancer properties.